Pengaruh Website Quality dan E-Service Quality terhadap Purchase Intention melalui Trust Platform Top Up Game - Fini Pandewidinata; Diena Noviarini; Fildzah Shabrina (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of website quality and e-service quality on purchase intention through trust among users of a game top-up platform. The study was motivated by increasing competition among game top-up platforms, requiring service providers to deliver high-quality websites and digital services capable of building user trust and encouraging purchase intention. This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to 183 users of the UPOINT.ID platform and analyzed using SEM-PLS with SmartPLS 4.0. The results indicate that website quality has a positive and significant effect on purchase intention (β = 0.317; p < 0.001), e-service quality has a positive and significant effect on purchase intention (β = 0.318; p < 0.001), and trust has a positive and significant effect on purchase intention (β = 0.314; p < 0.001). Furthermore, website quality (β = 0.586; p < 0.001) and e-service quality (β = 0.311; p < 0.001) also had positive and significant effects on trust. Mediation analysis revealed that trust significantly mediates the effects of both website quality and e-service quality on purchase intention. These findings suggest that improving website quality and e-service quality, along with strengthening user trust, is essential for enhancing purchase intention on game top-up platforms.